OVERVIEW AND COMPARATIVE ANALYSIS OF NIST COMPETITION FINALIST ALGORITHMS FOR LIGHTWEIGHT CRYPTOGRAPHY STANDARDIZATION - SHCHUR, NATALIIA; POKOTYLO, OLEKSANDRA; BAILIUK, YELYZAVETA (Herald of Khmelnytskyi National University. Technical sciences, 2023)
The shift from desktop computers to small devices brings a wide range of new security and privacy concerns. In many conventional cryptographic standards, the trade off between security, performance and resource requirements was optimized for desktop and server environments. As a result, implementing the current cryptography standards in resource-constrained devices becomes challenging due to the inherent limitations of such devices. Lightweight cryptography is an effective tool for the development of Internet of Things technologies, medical equipment, automotive electronics, and various other fields where balancing performance and security is crucial However, choosing the optimal cryptographic algorithm for lightweight cryptography remains a challenging task. That is why the main goal of the NIST competition is to select such lightweight cryptographic algorithms that would have low computational complexity, minimal memory usage, and low energy consumption, while providing a reliable level of protection for various applications. Typical cryptographic constructions and primitives upon which transformations in finalist algorithms are built are discussed. Specifications of finalist algorithms are examined, and their potential variants and modifications are analyzed. A comparison of algorithms based on various characteristics (key size, block size, tags, etc.) is presented, security indicators of each algorithm are given. The article aims to provide a general understanding of the design and properties of NIST competition finalist algorithms, aiding in the selection of the optimal algorithm for specific usage scenarios.